The Future of Small Farms : Synthesis Paper - Hazell, Peter (Washington, DC: World Bank, 2012)
Do small farms have a future in the developing world? Agriculture and small farms have played a major role in development and poverty reduction in the past, but changing global conditions and donor policies, and the characteristics of today's poor countries are widely acknowledged as making this much more difficult now. The paper develops a typology of country contexts in which the differing roles and needs for small scale agriculture development are considered. It clarifies current debates regarding (a) the potential for small farm development as a driver of growth and poverty reduction and (b) the roles of governments and the private sector in promoting such development.